Patterns : swirls - Maldonado, Gina Lorena (Hawthorn, VIC : Lake Press, 2018)
EARLY LEARNING: SIZE, SHAPES & PATTERNS. A fun early learning concept to help children identify patterns with bright an vibrant illustrations. Patterns are raised to add tactile, interactive element throughout each title. Ages 0+
Keywords: Pattern perception -- Pictorial works -- Juvenile literature; Swirls -- Juvenile literature; Children's stories; Board books